2022
DOI: 10.1016/j.heliyon.2021.e08690
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term (70 years) nitrogen fertilization and liming on carbon storage in water-stable aggregates of a semi-arid grassland soil

Abstract: Long-term N addition and liming did not affect bulk SOC content and stocks but lead to redistribution of C into water stable aggregates. Long-term N fertilization caused soil acidification and reduced mean weight diameter. Long-term N fertilization increased micro-aggregates and SOC stored in them. Long-term liming did not affect WSA, and C stored in them. Liming improved aggregation and increased C associated with large macro aggregates when co-applied with N fertilizers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Nitrogen had a negligible effect on the distribution of aggregates of different sizes in temperate grasslands (Y. Liu et al, 2022). However, long‐term nitrogen (N) fertilization may lead to disintegration of soil aggregates due to soil acidification by increasing monovalent ions (NH 4 + , H + ) and the reduction of microbial biomass carbon in a soil from semiarid grassland (Buthelezi & Buthelezi‐Dube, 2022; Guo et al, 2022). The previous study also reported that N additions improved the MWD of soil aggregates because of increases in the macro‐aggregate percentage and reductions in the silt‐clay portion, whereas the enhancement degree was variable in the terrestrial ecosystems, as well as the rate, form, and duration time of the N addition from a meta‐analysis (Lu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen had a negligible effect on the distribution of aggregates of different sizes in temperate grasslands (Y. Liu et al, 2022). However, long‐term nitrogen (N) fertilization may lead to disintegration of soil aggregates due to soil acidification by increasing monovalent ions (NH 4 + , H + ) and the reduction of microbial biomass carbon in a soil from semiarid grassland (Buthelezi & Buthelezi‐Dube, 2022; Guo et al, 2022). The previous study also reported that N additions improved the MWD of soil aggregates because of increases in the macro‐aggregate percentage and reductions in the silt‐clay portion, whereas the enhancement degree was variable in the terrestrial ecosystems, as well as the rate, form, and duration time of the N addition from a meta‐analysis (Lu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The YP anticipation in MF treatment under saturated conditions probably occurred because of an increase in particle repulsion forces caused by the higher content of monovalent ions than divalent ions in the soil sorptive complex (K/Ca + Mg). Long‐term experiments in different soil types and climatic conditions have already shown mineral fertilizer application, such as urea, reduces soil aggregation by causing soil acidification, Ca 2+ and Mg 2+ leaching and increases monovalent ions (NH 4 + and H + ) levels, especially in management systems with soil ploughing or in no‐till systems with legume planting (Blanco‐Canqui et al., 2014; Buthelezi & Buthelezi‐Dube, 2022; Guo et al., 2022; Haynes & Naidu, 1998). Our results also show acidification in the MF treatment, lower Ca 2+ and Mg 2+ levels and an increase in K + saturation (0–5 and 5–15 cm layers).…”
Section: Discussionmentioning
confidence: 99%
“…The pH decrease in soil media occurred after the addition of ammonium. According to Corley and Tinker (2016); Buthelezi and Buthelezi-Dube (2022), the addition of ammonium sulfate significantly decreases soil pH. This occurred through the oxidation of ammonium to nitrate in the soil media was followed by the release of H + ions, resulting in soil acidification (Msimbira and Smith 2020).…”
Section: Effect Of Ammonium Enrichment On Nitrification Activitymentioning
confidence: 99%